2010
DOI: 10.1002/cncr.25443
|View full text |Cite
|
Sign up to set email alerts
|

Higher parity and shorter breastfeeding duration

Abstract: BACKGROUND:The combination of increased parity and shorter breastfeeding duration might increase the odds of the least differentiated triple-negative breast cancer (BC) phenotype, theoretically because an expanded progenitor cell population from each pregnancy would incompletely differentiate postpartum. METHODS: Subjects consisted of a consecutive case series of 2473 women treated for invasive breast cancer between 2001 and 2006. Breast cancer phenotype (triple-negative BC, vs non-triple-negative BC) was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 36 publications
(55 reference statements)
3
43
0
Order By: Relevance
“…This is important because studies in Western populations have demonstrated that breast cancer is highly heterogeneous and risk factors may differ between different breast cancer subtypes [1921, 29, 30]. This study is also likely underpowered to draw conclusions about whether OCP use and HRT use are breast cancer risk factors in Vietnamese women, because the use of OCP and HRT in Vietnam has traditionally been much lower than in Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because studies in Western populations have demonstrated that breast cancer is highly heterogeneous and risk factors may differ between different breast cancer subtypes [1921, 29, 30]. This study is also likely underpowered to draw conclusions about whether OCP use and HRT use are breast cancer risk factors in Vietnamese women, because the use of OCP and HRT in Vietnam has traditionally been much lower than in Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…39 Development of TNBC in the absence or short duration of breastfeeding might be caused by progenitor cells in breast tissue not undergoing terminal differentiation and apoptosis that usually occurs with prolonged lactation, resulting in a persistent pool of progenitor cells that are at risk for carcinogenesis. 40 …”
Section: Epidemiological Risk Factorsmentioning
confidence: 99%
“…For example, absent or short duration of breastfeeding has been consistently associated with a higher risk of triple-negative non-IBC compared with the luminal A or ER+ defined subtypes of non-IBC (12,13, 16). Since the triple-negative subtype is overrepresented among IBC compared to non-IBC (7), identifying the risk factors for this aggressive tumor subtype and others is relevant for investigating biological mechanisms underlying the etiology of IBC and for developing strategies for subtype-specific breast cancer prevention (1,17).…”
Section: Introductionmentioning
confidence: 99%